Respuesta :

kanest
Assuming the expression reads:

[tex]\text{GCF of } 56f^3g^2, 70fg^3[/tex]

Isolate each term within each expression:

[tex]56f^3g^2 = 56 \times f^3 \times g^2[/tex]
[tex]70fg^3 = 70 \times f \times g^3[/tex]

Find the GCF for each like term:

[tex]\text{GCF of }56, 70 = 14[/tex]
[tex]\text{GCF of }f^3, f = f[/tex]
[tex]\text{GCF of } g^2, g^3 = g^2[/tex]

Combine the GCF terms together. The following expression will be your answer:

[tex]\boxed{14fg^2}[/tex]
GCF of 56 and 70 = 14
GCF of f and f3 = f
GCF of g2 and g3 is g2

Answer is 14fg2   Option c